Swine Influenza Virus Induces RIPK1/DRP1-Mediated Interleukin-1 Beta Production - Hong-Su Park; Guanqun Liu; Qiang Liu; Yan Zhou (Viruses, 2018)
Nucleotide-binding domain and leucine-rich repeat-containing protein 3 (NLRP3) inflammasome plays a pivotal role in modulating lung inflammation in response to the influenza A virus infection. We previously showed that the swine influenza virus (SIV) infection induced NLRP3 inflammasome-mediated IL-1β production in primary porcine alveolar macrophages (PAMs), and we were interested in examining the upstream signaling events that are involved in this process. Here, we report that the SIV-infection led to dynamin-related protein 1 (DRP1) phosphorylation at serine 579 and mitochondrial fission in PAMs. IL-1β production was dependent on the reactive oxygen species (ROS) production, and DRP1 phosphorylation resulted in the upregulation of the NLRP3 inflammasome. Furthermore, the requirement of the kinase activity of receptor-interacting protein kinase 1 (RIPK1) for the IL-1β production and RIPK1-DRP1 association suggested that RIPK1 is an upstream kinase for DRP1 phosphorylation. Our results reveal a critical role of the RIPK1/DRP1 signaling axis, whose activation leads to mitochondrial fission and ROS release, in modulating porcine NLRP3 inflammasome-mediated IL-1β production in SIV-infected PAMs.